Surgical treatment and survival of patients with invasive orbital tumors (Ukrainian Journal of Ophthalmology, 2023)
Background: Intraorbital tumor invasion is not uncommon among craniofacial tumors, and is seen in 27% of cases. Craniofacial malignancies account for 3% of all head and neck tumors. Malignant tumors are more common than benign and comprise about 73% of all craniofacial tumors with intraorbital invasion. Their growth is aggressive and invasive, leading to early postoperative recurrence. The survival of patients with malignant craniofacial tumors depends largely on orbital invasion, and patients demonstrating orbital invasion had a 40% survival rate, while patients without had a survival rate of 72%. Patients with total resection of craniofacial tumors (including those with intraorbital extensions) show higher non-recurrence and survival rates than patients without total resection. Orbital exenteration does not provide patients with better survival rates and worsened the quality of life.Purpose: To assess the outcomes of surgical treatment for, and the survival of patients with, malignant craniofacial tumors growing into the orbit.Material and Methods: We reviewed the outcomes of surgical treatment for, and the survival of 94 patients with, malignant craniofacial tumors growing into the orbit.Results: Destruction of the bony orbital wall only (without periorbital adhesion), was seen in 27/94 cases (28.7%), whereas periorbital invasion, in 67/94 cases (71.3%). The tumor was excised completely with visually clear margins in all cases. Patient survival was affected by the degree of orbital invasion. The recurrence rate after surgery for malignant craniofacial tumors growing into the orbit was 44.7% (40/94 patients). Ten patients had a local intraorbital recurrence after surgery for malignant craniofacial tumors growing into the orbit.Conclusion: Periorbital invasion was seen in 71.3% of patients with malignant craniofacial tumors. There was no significant difference in the survival of patients with malignant craniofacial tumors of different histology. Orbital exenteration does not improve survival and recurrence in patients with malignant craniofacial tumors with orbital invasion. In patients with preoperative periorbital invasion and further intraorbital extension, the recurrence rate was more than three-fold higher than in those showing only destruction of the bony orbital wall preoperatively.
Keywords: malignant craniofacial tumors; orbital invasion; transbasal approach; subcranial approach; orbital exenteration